The Problem of Space and Time in Philosophy - Meškauskas, Eugenijus (Problemos, 1977)
The article deals with the theoretical premises of the emergence of the problem of the objectiveness of space and time forms in philosophy in connection with idealistic or agnostic opposition of human perception of reality to its objective essence. The author maintains that the subjective interpretation of space and time arises, on the one hand, from their identification with their mathematical constructions and, on the other hand, from the interpretation of objectivity, negated in terms of its independent existence.